Renewable energy as an airport revenue source - Barrett, Stephen B.; DeVita, Philip M.; Whiteman, Adam (ACRP report, 2015)
"TRB's Airport Cooperative Research Program (ACRP) Report 141: Renewable Energy as an Airport Revenue Source explores challenges airports may anticipate when considering renewable energy as a revenue source. These considerations include the airport's geography and terrain, infrastructure, real estate, energy costs, public policy, regulatory and compliance requirements, tax credits, sponsor assurances, ownership, impacts to navigation and safety, security, staffing issues, and many others. The guidebook also includes detailed financial information on the cost and performance of projects that have been implemented by airports. The guidebook also includes an appendix available online that provides sample a request for proposals."--